Identification of galectin-9 and its antibacterial function in Yellow River carp (Cyprinus carpio haematopterus) - Wang, Li; Hu, Yuanyuan; Li, Xudong; Zhang, Ziyan; Wang, Nan; Chao, Limin; Li, Chengfei; Gao, Pei; Ma, Jinyou; Wang, Lei; Xia, Xiaojing (Frontiers in Immunology, 2025)
IntroductionGalectin-9 is a β-galactoside-binding lectin that functions as a critical pattern recognition receptor (PRR) in the host immune system, initiating immune defense responses by recognizing and binding to pathogen-associated molecular patterns (PAMPs) on the surface of microorganisms. In this study, we identified and characterized a novel galectin-9 cDNA, designated CcGal-9, from Yellow River carp (Cyprinus carpio haematopterus).MethodsThe full-length CcGal-9 cDNA was cloned and sequenced, and its structural features were analyzed. Tissue distribution of CcGal-9 mRNA was examined by quantitative real-time PCR. Expression changes following Aeromonas hydrophila and Staphylococcus aureus infections were evaluated. Recombinant CcGal-9 (rCcGal-9) was expressed in Escherichia coli BL21 (DE3), purified, and assessed for binding to various PAMPs and microorganisms. Agglutination assays and survival experiments were conducted to determine functional roles in immune defense. ResultsThe CcGal-9 cDNA is 963 bp in length and encodes a 320-amino acid protein with two distinct carbohydrate recognition domains (CRDs), characteristic of tandem-repeat type galectins. CcGal-9 mRNA was predominantly expressed in the spleen, testicle, and head kidney, with lower levels in the liver and intestine. Upon bacterial infection, CcGal-9 expression was significantly upregulated in multiple immune-related tissues. Purified rCcGal-9 bound LPS, PGN, mannan, and both Gram-positive and Gram-negative bacteria, and exhibited broad-spectrum agglutination activity. Administration of rCcGal-9 markedly improved the survival rate of carp challenged with A. hydrophila. DiscussionThese findings indicate that CcGal-9 is an important PRR in C. carpio, contributing to immune defense against pathogenic microorganisms through PAMP recognition and microbial agglutination. This study enhances our understanding of galectin-mediated immunity in teleost fish.